Bacteriophage Adsorption: Likelihood of Virion Encounter with Bacteria and Other Factors Affecting Rates - Stephen Tobias Abedon (MDPI AG, 2023)
For ideal gasses, the likelihood of collision of two molecules is a function of concentrations as well as environmental factors such as temperature. This too is the case for particles diffusing within liquids. Two such particles are bacteria and their viruses, the latter called bacteriophages or phages. Here, I review the basic process of predicting the likelihoods of phage collision with bacteria. This is a key step governing rates of phage-virion adsorption to their bacterial hosts, thereby underlying a large fraction of the potential for a given phage concentration to affect a susceptible bacterial population. Understanding what can influence those rates is very relevant to appreciating both phage ecology and the phage therapy of bacterial infections, i.e., where phages are used to augment or replace antibiotics; so too adsorption rates are highly important for predicting the potential for phage-mediated biological control of environmental bacteria. Particularly emphasized here, however, are numerous complications on phage adsorption rates beyond as dictated by the ideals of standard adsorption theory. These include movements other than due to diffusion, various hindrances to diffusive movement, and the influence of assorted heterogeneities. Considered chiefly are the biological consequences of these various phenomena rather than their mathematical underpinnings.